PALANG MERAH REMAJA SEBAGAI WADAH PENGEMBANGAN PERILAKU MENOLONG DI KALANGAN SISWA SMA NEGERI 9 SEMARANG - Rochmawati, Eka (Solidarity: Journal of Education, Society and Culture, 2013)
Helping behavior is very important in everyday life. However, the current behavior is difficult to find help in everyday life. Helping behavior are difficult to find in todays youth, especially in urban environments. Adolescents is one of the next generation involved in the moral development of Indonesia. School is a place of moral cultivation. School held a variety of extracurricular activities to channel the talents and interests of each child. PMR is one of the extracurricular activities related to the humanitarian field. PMR activities related to the distribution, development and application of behavior to help students. PMR 9 SMA Negeri Semarang is one of the active conducting extracurricular social activities. The purpose of this study is to determine the implementation of the Youth Red Cross activities among high school students in District 9 Semarang and also observe the activities of the Red Cross Youth in driving behaviors to help high school students Semarang District 9. This study uses qualitative methods. The validity of the data used is the technique of data triangulation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the Red Cross Youth Senior High School 9 Semarang held every Thursday at 3:00 p.m. to 5:00 pm. PMR organized activities to encourage behaviors to help high school students Semarang District 9.